2019
DOI: 10.2147/cia.s208102
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of a behavioral medicine intervention on pain, health, and behavior among community-dwelling older adults: a randomized controlled trial</p>

Abstract: Purpose The aim of the study was to evaluate the effects of an intervention, based on a behavioral medicine approach in physical therapy (BMPI), on pain-related disability and physical performance as well as on pain severity, pain catastrophizing, physical activity levels, falls efficacy, and health-related quality of life (HRQL) by comparing the effects to standard care. Patients and methods The study was a pragmatic randomized controlled trial with a two-group design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 61 publications
(77 reference statements)
4
24
0
1
Order By: Relevance
“…46 In a study investigating the effect of a behavioral medicine approach of physical therapy that addresses physical function and psychosocial factors for older adults with chronic pain, it was noted that such a program resulted in a greater decrease in pain severity, as well as greater improvements in physical activity, health-related quality of life and self-efficacy in the intervention group, compared to the control group. 47 Interestingly, and similar to the results in the present study, both persons in the intervention and control group demonstrated significant improvements in physical function. 47 In the present study, the functional gains measured for gait, balance and functional autonomy following outpatient rehabilitation were not associated with initial pain levels.…”
Section: Pain Intensity and Functional Outcomessupporting
confidence: 89%
See 3 more Smart Citations
“…46 In a study investigating the effect of a behavioral medicine approach of physical therapy that addresses physical function and psychosocial factors for older adults with chronic pain, it was noted that such a program resulted in a greater decrease in pain severity, as well as greater improvements in physical activity, health-related quality of life and self-efficacy in the intervention group, compared to the control group. 47 Interestingly, and similar to the results in the present study, both persons in the intervention and control group demonstrated significant improvements in physical function. 47 In the present study, the functional gains measured for gait, balance and functional autonomy following outpatient rehabilitation were not associated with initial pain levels.…”
Section: Pain Intensity and Functional Outcomessupporting
confidence: 89%
“…47 Interestingly, and similar to the results in the present study, both persons in the intervention and control group demonstrated significant improvements in physical function. 47 In the present study, the functional gains measured for gait, balance and functional autonomy following outpatient rehabilitation were not associated with initial pain levels. The changes in the values of the outcome measures between T1 and T2 were similar between the groups.…”
Section: Pain Intensity and Functional Outcomessupporting
confidence: 89%
See 2 more Smart Citations
“…Studies that contributed to the results were from Australia, 51 Ireland, 40 Norway, 9 , 10 , 56 , 57 Sweden, 4 , 6 , 8 , 19 , 23 , 28 , 34 , 35 , 42 , 43 , 45 , 49 the United Kingdom, 27 , 58 and the United States. 3 , 44 …”
Section: Resultsmentioning
confidence: 99%